Small potatoes? Not for Rwanda’s potato seed system - International Institute of Tropical Agriculture (International Institute of Tropical Agriculture, 2024)
Demand for new potato seed varieties continues to rise steadily in Rwanda, with AID-I GLR contributing to this rise. In this video, Mr Theophile Ndacyayisenga, Potato Breeder at Rwanda Agriculture and Animal Resources Development Board (RAB), tells us about this evolution, connecting potato breeding in 1984 to developments four decades later, now, in 2024.